Kontribusi Program Keluarga Harapan (PKH) dalam Mendukung Sustainable Development Goals (SDGs) - Mayesa Yuswijayanti; Ali Akbarjono; Sepri Yunarman; Rossi Delta Fitrianah (Yayasan Darussalam Bengkulu, 2026)
This study analyzes the contribution of the Program Keluarga Harapan (PKH) toward achieving Sustainable Development Goals (SDGs) at the local level through the perspective of policy implementation. The research is based on the assumption that the success of social protection programs is not solely determined by policy design, but also by the quality of implementation within specific social contexts. This study employed a qualitative approach with a descriptive design conducted in Kelurahan Durian Depun, Kecamatan Merigi, Kabupaten Kepahiang. Informants were selected purposively and developed through snowball sampling, consisting of PKH facilitators, village officials, beneficiary families (KPM), and non-beneficiary community members. Data were collected through semi-structured interviews, observation, and documentation, then analyzed using the interactive model of Miles et al. through data reduction, data display, and conclusion drawing. The findings indicate that PKH implementation administratively has been carried out according to procedural standards through cash assistance distribution, P2K2 mentoring activities, and monitoring of education and health obligations. However, procedural compliance has not fully produced substantive changes in economic independence and long-term social transformation. The program contributes positively to improving access to education and health services, supporting SDG 3 and SDG 4, as well as reducing household expenditure burdens related to SDG 1. Nevertheless, the contribution remains conditional because the effectiveness of the program is strongly influenced by communication, facilitator capacity, bureaucratic coordination, and the participation level of beneficiary families. Structural factors such as employment conditions, age, health limitations, and accessibility also affect beneficiary involvement in mentoring activities. Therefore, PKH in the research location tends to function more as a social protection instrument than as an empowerment mechanism. The study concludes that the success of PKH should not only be measured through administrative compliance and aid distribution, but also through its ability to create sustainable socio-economic transformation and reduce dependency on social assistance.